Digital geographies of austerity: young men's material, affective and everyday relationships with the digital - Bonner-Thompson, C; McDowell, L (Elsevier, 2021)
The ways that people must now manage and negotiate the uncertainty of austerity involves access to the internet, digital devices and the skills to use them. The Universal Credit welfare system in the UK, for example is now online, however access and skills can be uncertain or sporadic for some. At the same time, digital technology is not simply a ‘way out’ of precarious situations and many people have ambivalent relationships with ‘the digital’, including some of the 40 young white working-class men we interviewed living in physically isolated coastal towns in England, after a decade of austerity policies have added to their socio-economic exclusion. Here, we explore how the digital is folded into patterns of uncertainty and insecurity through an examination of the material, affective and everyday relationships that young men have with digital technologies. We add to arguments about the geographies of austerity by exploring the spatial and temporal patterns that emerge as young men attempt to access the internet. We also contribute to the growing field of digital geographies by exploring the contradictory emotional and affective relationship young men have with digital technologies, to highlight how the digital always emerges in relation of power, producing new forms of inequality and identities. We argue that geographers must remain sensitive to these complex and contradictory relationships with digital technologies if they are to be used to disrupt processes of marginalisation, exclusion and uncertainty.